Pahang Dialogue discusses ECRL development impact on socio-economic population - Mimi Rabita, Abdul Wahit (2020)
Kuantan, 23 July 2020 - More systematic road construction planning taking into account the importance and overflow to residents and related parties, especially in terms of infra stability and future maintenance costs are among the resolutions discussed in the East Coast Rail Link project development roundtable conference (ECRL): Socio-Economic Impact on Pahang State Population Organized by Pahang State Government and Universiti Malaysia Pahang (UMP).